Teachers' Creativity in Shaping the Character of Students at Madrasah Diniyah Takmiliyah Awaliyah - Baswita, Yayuk; Zulfamanna, Zulfamanna; Ilham, Seprian (Ahlussunnah: Journal of Islamic Education, 2025)
This study aims to analyze teachers' creativity in shaping the character of students at Madrasah Diniyah Takmiliyah Awaliyah. The urgency of this study stems from the need to strengthen character education in non-formal Islamic educational institutions amid social challenges and technological developments. This study uses a qualitative approach with a phenomenological design. Data were collected through in-depth interviews, observations, and documentation with key informants, namely the madrasah principal, teachers, and students. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that teacher creativity is manifested through a variety of learning methods, the use of simple learning media, exemplary attitudes, and continuous religious habits. These practices contribute to shaping students' religious character, discipline, responsibility, and social awareness. These findings confirm that teacher creativity is a strategic factor in the success of character education at Madrasah Diniyah Takmiliyah Awaliyah and needs to be systematically supported by educational institutions and the social environment.